MEMBANGUN JARINGAN VIRTUAL PRIVATE NETWORK (VPN) DENGAN METODE TUNNELING MENGGUNAKAN MIKROTIK UNTUK KOMUNIKASI LOKAL DI STMIK PPKIA PRADNYA PARAMITA MALANG - Habibi, Ahmad; Arifin, Samsul (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
MikroTik RouterOS â¢ is the operating system and which can be used to make the computer even become a reliable network routers , includes a comprehensive range of features for network and wireless , one of the reliable features is a VPN ( Virtual Private Network ) .VPN ( Virtual Private Network ) is a way to create a network is